Paulus Vladimiri and Stanislaus de Scarbimiria – medieval Krakow law school and the Polish contribution to the formation of the rights of nations - Jacek Grzybowski (Chrześcijaństwo-Świat-Polityka)
The formation of medieval national communities constitutes the basis of political and cultural European history. However, it is almost forgotten nowadays that a significant contribution to reflections on sovereignty was made by Polish scholars. Stanisław of Skarbimierz (Stanislaus de Scarbimiria – 1365-1431) and Paweł Włodkowic (Paulus Vladimiri – 1370-1435), medieval Cracovian jurists and philosophers, are rather unknown in the Western milieu. Both of them added their voices to one of the most important disputes for European political culture. The 15th-century debate between Jagiellonian Poland and the Teutonic Order that conquered the Prussian lands became the basis for Polish lawyers to develop an ingenuous theory concerning human rights and the rights of nations.  Stanisław of Skarbimierz and Paweł Włodkowic, the founders of the Polish school of law at the Cracow Academy, in their writings and letters, firmly demonstrated injustice, the breaking of basic human rights, injuries, and other crimes perpetrated by the Teutonic knights against the Prussians, Lithuanians, Yotvingians and Poles. The scholars elaborated on the most important problems of law and international relationships, concerning the issues of human rights, the right to self-determination, just war, respect for personal property and human dignity. The doctrine of the Polish School of international law elaborated by Paul Wladimiri and Stanislaw of Skarbimierz have had and still make a considerable impact on the understanding of human rights and rights of nations. Their works and sermons espouse the craving for international justice, while securing national interests, and for a model of Europe as a “family of independent and sovereign nations” whose coexistence is founded on the Christian anthropology according to which a man as endowed by God with dignity and freedom. The works of the Cracovian masters should impress us and make proud of our legacy, while in Europe they should awaken interest and creative thought.